Emotional Competencies of Students and Psycholinguistic Characteristics of Their Texts Written under Conditions of Situational Stress: Relationship Issues - Irina V. Belasheva (Peoples' Friendship University of Russia (RUDN University), 2022)
The author deals with the relationship between the psycholinguistic characteristics of the text, as indicators of psycho-emotional states in conditions of situational stress, and the level of developed emotional competencies, i.e., the ability to understand and manage one's own and others' emotions. An empirical study was conducted on a student sample using the EmIn Questionnaire by D.V. Lyusin, the State-Trait Anxiety Inventory (STAI) by Ch.D. Spielberger and the Prognoz-2 Questionnaire by V.Yu. Rybnikov. The students who took part in the experiment wrote texts under situational stress, for which psycholinguistic indicators were calculated. The results of the study were analyzed using Spearman's rank correlation coefficient. The data obtained confirmed the positive relationship between the emotional competencies of the students under conditions of situational stress and such psycholinguistic characteristics of their written texts as the Treiger index, the action objectification index, the use of the "subject of assistance" syntaxeme, which reflect emotional and cognitive tension, desire and determination to act and help others, as well as the negative relationship with the coefficient of aggressiveness, the first person singular pronouns, the use of the "predicate" and "causative" syntaxemes, which are markers of uncontrolled aggression, suspicion, egocentric position, search for emotional positive support from the outside, and avoidance reactions. The assumption about the relationship of emotional competences with manifestations of situational ("state") and personal ("trait") anxiety, as well as the likelihood of neuropsychic breakdowns in a stressful situation, was not confirmed. As a result of the study, general psycholinguistic indicators of the manifestations of situational anxiety and the formation of emotional competences were determined - these are the action objectification index and aggressiveness index. This suggests that both the ability to understand and regulate the emotions of other people, and situational anxiety, as a reactive state of the subjective experience of anxiety, tension, concern, when writing a text in a stressful situation, can be marked by an increase in number of verbs and verb forms used in the text, syntactic incompleteness of statements and a decrease in their socialization.